2004
DOI: 10.1111/j.1365-2443.2004.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation status dependent function of FOG‐1

Abstract: The molecular interactions between transcription factors and cofactors play crucial roles in various biological processes, including haematopoiesis. FOG-1 is a cognate cofactor of GATA-1, and the FOG-1/GATA-1 complex is essential for the haematopoietic differentiation of erythroid cells and megakaryocytes. In order to elucidate the biological functions of FOG-1 in the different contexts of cell differentiation, we analysed the effects of FOG-1 expression on haematopoietic cell differentiation, using a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…33 A research method combining in vitro ES cell differentiation with tetracycline-based conditional gene expression is a powerful tool for analyzing the functions of various genes at distinct stages of hematopoietic development and differentiation. 24,[34][35][36] In a previous in vitro study using mouse ES cells cocultured on the stromal cell line OP9, we demonstrated that GATA-2 increased the proliferation of immature hematopoietic cells. 24 In the present study, we used the OP9 stroma cell-based differentiation method to examine the effects of GATA-2 on the development of macrophages from ES cells.…”
Section: Introductionmentioning
confidence: 82%
“…33 A research method combining in vitro ES cell differentiation with tetracycline-based conditional gene expression is a powerful tool for analyzing the functions of various genes at distinct stages of hematopoietic development and differentiation. 24,[34][35][36] In a previous in vitro study using mouse ES cells cocultured on the stromal cell line OP9, we demonstrated that GATA-2 increased the proliferation of immature hematopoietic cells. 24 In the present study, we used the OP9 stroma cell-based differentiation method to examine the effects of GATA-2 on the development of macrophages from ES cells.…”
Section: Introductionmentioning
confidence: 82%
“…DNA content analysis was performed using propidium iodide (PI) as described previously. 41 Cell-cycle distribution was analyzed using ModFit LT software (Becton Dickinson).…”
Section: Flow Cytometry Analysis and Cell Sortingmentioning
confidence: 99%
“…The functions of transcription factors are presumably diversified based on the cell differentiation status. 41 An experimental system combining a null mutation with the conditional expression of the gene is the most suitable way to analyze these functions. In vivo rescue experiments have been reported for only a few genes, presumably because the experiments are difficult to perform.…”
Section: Merits and Limitations Of The Experimental System Using Es Cmentioning
confidence: 99%
“…Conditional manipulation of gene expression enables us to analyze gene function at distinctive stages of hematopoietic differentiation from hESCs, which has not been shown previously, although it was reported by several groups in mouse embryonic stem cells. 32,33 By sequentially infecting H1 cells with rtTA and inducible miRs-126/126* expressing lentiviral vectors ( Figure 3A), we established several hESC lines conditionally expressing miRs-126/ 126* (I-miRs-126/126*). All experiments were performed on 2 independently derived lines, and they produced comparable results.…”
Section: Generation Of Inducible Mirs-126/126* Overexpressing Hescsmentioning
confidence: 99%